Paperless Online Banking (e-Cheque Imaging) - Mustafa, Mahdi (N. F) B. (2008)
This study aims to highlight the importance of using e-cheque imaging in e-business and e-banking. E-cheque imaging enables both the customer and the bank to have more flexible accessible valid transactions by electronically checking all transactions through an online bank web system. The researcher developed a prototype for e-cheque imaging system and adopted the research in general design methodology in order to make the transaction cheque clearing process more efficient and accurate. After testing the system, the findings revealed that the proposed system is capable to record a successful complete electronic transaction. By developing such a system, the study attempts to confirm that there are many potential benefits that can be obtained from applying E-cheque imaging.